Deficiency of Stabilin-1 in the context of hepatic melanoma metastasis - Wohlfeil, Sebastian A.; Olsavszky, Ana; Irkens, Anna Lena; Häfele, Verena; Dietsch, Bianca; Straub, Niklas; Goerdt, Sergij; Géraud, Cyrill (Cancers, 2024)
Background: This study analyzed the role of Stabilin-1 on hepatic melanoma metastasis in preclinical mouse models. Methods: In Stabilin-1−/− mice (Stab1 KO), liver colonization of B16F10 luc2 and Wt31 melanoma was investigated. The numbers, morphology, and vascularization of hepatic metastases and the hepatic microenvironment were analyzed by immunofluorescence. Results: While hepatic metastasis of B16F10 luc2 or Wt31 melanoma was unaltered between Stab1 KO and wildtype (Ctrl) mice, metastases of B16F10 luc2 tended to be smaller in Stab1 KO. The endothelial differentiation of both types of liver metastases was similar in Stab1 KO and Ctrl. No differences in initial tumor cell adhesion and retention to the liver vasculature were detected in the B16F10 luc2 model. Analysis of the immune microenvironment revealed a trend towards higher levels of CD45+Gr-1+ cells in Stab1 KO as compared to Ctrl in the B16F10 luc2 model. Interestingly, significantly higher levels of POSTN were found in the matrix of hepatic metastases of Wt31, while liver metastases of B16F10 luc2 showed a trend towards increased deposition of RELN. Conclusions: Hepatic melanoma metastases show resistance to Stabilin-1 targeting approaches. This suggests that anti-Stab1 therapies should be considered with respect to the tumor entity or target organs.